2020
DOI: 10.3390/jcm9061860
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatment of Advanced Pancreatic Neuroendocrine Neoplasms

Abstract: Pancreatic neuroendocrine neoplasms (panNENs) are relatively rare but their incidence has increased almost sevenfold over the last four decades. Neuroendocrine neoplasms are classified according to their histologic differentiation and their grade. Their grade is based on their Ki-67 proliferation index and mitotic index. Their prognosis is highly variable according to these elements and treatments also vary according to their classification. Surgery is the only curative treatment for localized and advanced pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…It has been reported that platinum-based chemotherapy in NET G3 demonstrates a lower response rate than in NEC [12], but there are no previous reports describing the use of molecular targeted therapy and STZ for NET G3. In general, STZ and molecular targeted therapy are used for unresectable NENs [13], but an optimal treatment for NET G3 has not been established. Therefore, while attempting to treat NET G3 according to the conventional treatment for NET G1/G2, collecting the treatment results of NET G3 cases is important in attempting to establish the optimal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that platinum-based chemotherapy in NET G3 demonstrates a lower response rate than in NEC [12], but there are no previous reports describing the use of molecular targeted therapy and STZ for NET G3. In general, STZ and molecular targeted therapy are used for unresectable NENs [13], but an optimal treatment for NET G3 has not been established. Therefore, while attempting to treat NET G3 according to the conventional treatment for NET G1/G2, collecting the treatment results of NET G3 cases is important in attempting to establish the optimal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection can be performed in about 15–20% of the patients at the time of diagnosis [ 2 ]. In the remaining patients with locally advanced or metastatic disease, palliative treatments are required [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Moreover, pancreatic surgery is one of the most complex surgical abdominal procedures, which is due to anatomical location of the pancreatic gland, close to vascular structures and the biliary and gastrointestinal system.…”
Section: Introductionmentioning
confidence: 99%
“…The NORDIC study reported a low response rate to platinum-based chemotherapy for high-grade NENs with a Ki-67 < 55%, and this was subsequently confirmed in multiple small cohort studies 1,5–7,12,13 . On the other hand, alkylator-based chemotherapy is an established treatment option even for low-grade pancreatic NETs, which are regarded as chemosensitive tumors, unlike midgut NETs 16,17 . The role of surgical management and other local therapies for G3 NETs is also controversial, as it is often indicated in G1–2 NETs but contraindicated for NECs 4,6,10,18 …”
mentioning
confidence: 99%
“…1,[5][6][7]12,13 On the other hand, alkylator-based chemotherapy is an established treatment option even for low-grade pancreatic NETs, which are regarded as chemosensitive tumors, unlike midgut NETs. 16,17 The role of surgical management and other local therapies for G3 NETs is also controversial, as it is often indicated in G1-2 NETs but contraindicated for NECs. 4,6,10,18 Clinical decision making for this rare disease is complex and based on limited data.…”
mentioning
confidence: 99%